A five-day ward as part of a comprehensive surgical service. Issue 6275 (9th May 1981) - Ruckley, C V; Ferguson, J B; Cuthbertson, C
Abstract : The role of a five-day ward was examined as part of an audit of the work of a general surgical unit. The four levels of care for elective operations were main ward, five-day ward, major day care, and minor day care. In a prospective study 2000 consecutive patients were followed through their hospital courses from the first referral to the surgical clinic to the postoperative follow-up visit. The aim was to measure the surgical needs of this population and to determine the rates of success or failure in carrying through the planned care. One thousand and forty-five (52%) of the referred patients were put on waiting lists, and of these, 975 (93%) completed their hospital course within the two years of the study. The surgeons chose five-day ward care for 28% of the patients, major and minor day care for 8% and 33% respectively, leaving only 30% who were judged to require care in the main ward. Selections were validated by postoperative interview, which showed that 82% had followed the expected hospital course, and by monitoring deviations from planned care. Four per cent of the five-day ward patients required transfer to the main ward and 3.3% required readmission. Patients managed in the five-day ward were on average younger and the conditions less urgent than those in the main ward. We conclude that a five-day ward can fulfil a large and important part of a general surgical service provided that its function is closely integrated with other parts of the service and that patients are accurately assessed in the outpatient clinic.